Difference between revisions of "Math 22 Logarithmic Functions"
Jump to navigation
Jump to search
(6 intermediate revisions by the same user not shown) | |||
Line 18: | Line 18: | ||
2.<math>e^{\ln x}=x</math> | 2.<math>e^{\ln x}=x</math> | ||
+ | 3.<math>\ln{xy}=\ln{x}+\ln{y}</math> | ||
+ | |||
+ | 4.<math>\ln{\frac{x}{y}}=\ln x - \ln y</math> | ||
+ | |||
+ | 5.<math>\ln{x^n}=n\ln x</math> | ||
+ | |||
+ | |||
+ | |||
+ | '''Exercises 1''' Use the properties of logarithms to rewrite the expression as the logarithm of a single quantity | ||
+ | |||
+ | '''a)''' <math>\ln(x-2)-\ln(x+2)</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\ln(x-2)-\ln(x+2)=\ln \frac{x-2}{x+2}</math> | ||
+ | |} | ||
+ | |||
+ | '''b)''' <math>5\ln (x-6)+\frac{1}{2}\ln(5x+1)</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>5\ln(x-6)+\frac{1}{2}\ln(5x+1)=\ln(x-6)^5+\ln[(5x+1)^{\frac{1}{2}}]=\ln [(x-6)^5\sqrt{5x+1}]</math> | ||
+ | |} | ||
+ | |||
+ | '''c)''' <math>3\ln x+2\ln y -4\ln z</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\ln x^3 + \ln y^2 -\ln z^4=\ln\frac{x^3y^2}{z^4}</math> | ||
+ | |} | ||
+ | |||
+ | '''d)''' <math>7\ln (5x+4)-\frac{3}{2}\ln (x-9)</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>7\ln (5x+4)-\frac{3}{2}\ln (x-9)=\ln (5x+4)^7-\ln (x-9)^{\frac{3}{2}}=\ln\frac{(5x+4)^7}{(x-9)^{\frac{3}{2}}}</math> | ||
+ | |} | ||
+ | |||
+ | '''Exercises 2''' Solve for x. | ||
+ | |||
+ | '''a)''' <math>\ln(2x)=5</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\ln(2x)=5</math>, so <math>e^5=2x</math>, hence <math>x=\frac{e^5}{2}</math> | ||
+ | |} | ||
+ | |||
+ | '''b)''' <math>5\ln x=3</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>5\ln x=3</math>, so <math>ln {x^5}=3</math>, so <math>e^3=x^5</math>, hence <math>x=\sqrt[5]{e^3}</math> | ||
+ | |} | ||
Latest revision as of 08:44, 11 August 2020
Logarithm Function
The logarithm is defined as if and only if
Definition of the Natural Logarithmic Function
The natural logarithmic function, denoted by , is defined as if and only if
Properties of the Natural Logarithmic Function
Let 1. The domain of is and the range of is 2. The x-intercept of the graph of is 3. The function is continuous, increasing, and one-to-one. 4. and
Inverse Properties of Logarithms and Exponents
1. 2. 3. 4. 5.
Exercises 1 Use the properties of logarithms to rewrite the expression as the logarithm of a single quantity
a)
Solution: |
---|
b)
Solution: |
---|
c)
Solution: |
---|
d)
Solution: |
---|
Exercises 2 Solve for x.
a)
Solution: |
---|
, so , hence |
b)
Solution: |
---|
, so , so , hence |
This page were made by Tri Phan